Oxygen-generating microparticles downregulate HIF-1α expression, increase cardiac contractility, and mitigate ischemic injury. (15th March 2023) - Mandal, Kalpana; Sangabathuni, Sivakoti; Haghniaz, Reihaneh; Kawakita, Satoru; Mecwan, Marvin; Nakayama, Aya; Zhang, Xuexiang; Edalati, Masoud; Huang, Wei; Lopez Hernandez, Ana; Jucaud, Vadim; Dokmeci, Mehmet R.; et al.
Abstract: Myocardial hypoxia is the low oxygen tension in the heart tissue implicated in many diseases, including ischemia, cardiac dysfunction, or after heart procurement for transplantation. Oxygen-generating microparticles have recently emerged as a potential strategy for supplying oxygen to sustain cell survival, growth, and tissue functionality in hypoxia. Here, we prepared oxygen-generating microparticles with poly D, L-lactic-co-glycolic acid, and calcium peroxide (CPO), which yielded a continuous morphology capable of sustained oxygen release for up to 24 h. We demonstrated that CPO microparticles increased primary rat cardiomyocyte metabolic activity while not affecting cell viability during hypoxia. Moreover, hypoxia-inducible factor (HIF)-1α, which is upregulated during hypoxia, can be downregulated by delivering oxygen using CPO microparticles. Single-cell traction force microscopy data demonstrated that the reduced energy generated by hypoxic cells could be restored using CPO microparticles. We engineered cardiac tissues that showed higher contractility in the presence of CPO microparticles compared to hypoxic cells. Finally, we observed reduced myocardial injuries in ex vivo rabbit hearts treated with CPO microparticles. In contrast, an acute early myocardial injury was observed for the hearts treated with control saline solution in hypoxia. In conclusion, CPO microparticles improved cell and tissue contractility and gene expression while reducing hypoxia-induced myocardial injuries in the heart. Statement of significance: Oxygen-releasing microparticles can reduce myocardial ischemia, allograft rejection, or irregular heartbeats after heart transplantation. Here we present biodegradable oxygen-releasing microparticles that are capable of sustained oxygen release for more than 24 hrs. We then studied the impact of sustained oxygen release from microparticles on gene expresseion and cardiac cell and tissue function. Previous studies have not measured cardiac tissue or cell mechanics during hypoxia, which is important for understanding proper cardiac function and beating. Using traction force microscopy and an engineered tissue-on-a-chip, we demonstrated that our oxygen-releasing microparticles improve cell and tissue contractility during hypoxia while downregulating the HIF-1α expression level. Finally, using the microparticles, we showed reduced myocardial injuries in rabbit heart tissue, confirming the potential of the particles to be used for organ transplantation or tissue engineering. Graphical Abstract: Image, graphical abstract